Three‐dimensional ultrashort echo‐time imaging using a FLORET trajectory. Issue 3 (24th October 2016) - Robison, Ryan K.; Anderson, Ashley G.; Pipe, James G.
Abstract : Purpose: Three‐dimensional ultrashort echo‐time (UTE) imaging commonly makes use of an isotropic 3D radial projection acquisition. The FLORET sequence is proposed and evaluated as a more efficient alternative.Methods: The properties of the FLORET trajectory are contrasted with those of a 3D radial projection trajectory. The theoretical advantages of FLORET, including greater sampling and SNR efficiency, are evaluated based upon experimental data. The effect of T 2 * decay on FLORET is analyzed in comparison to the 3D radial, Cones, and Density Adapted Radial trajectories. FLORET UTE image quality is compared with 3D radial UTE image quality. Results: FLORET is shown to have several advantages over 3D radial acquisitions with respect to image quality, scan time, signal‐to‐noise, and off‐resonance blurring for UTE data. The signal and resolution losses from T 2 * decay for a FLORET acquisition are shown to be comparable to those of Density Adapted Radial and Density Compensated Cones trajectories. Conclusion: The FLORET sequence is recommended as an alternative to 3D radial projection sequences for musculoskeletal UTE imaging as well as other UTE applications that accommodate modest to long per shot sampling times. FLORET is not recommended for imaging extremely short T 2 species such as dentin. Magn Reson Med 78:1038–1049, 2017. © 2016 International Society for Magnetic Resonance in Medicine